Establishing entrepreneurship education with a bottom-up approach: insights from a longitudinal case study. (10th May 2010) - Testa, Stefania
This paper focuses on the process of establishing an entrepreneurial course with a bottom-up approach, i.e., under the leadership of an entrepreneur. Such initiatives are rather uncommon given that most resources are deployed in top-down approaches that emphasise institutional actors. The paper's objectives are as follows: 1) to discuss the evolution of the course, underpinning the relevant changes that have been introduced since the course was started; 2) to identify the determinants for discontinuance and to highlight the difficulties encountered. The different foci and actions, and what the key characteristics of the entrepreneurship course were over the different periods of the process, are explored in detail. On the basis of the collected evidence, it can be argued that the initiative achieved quite interesting results despite a lack of significant collaboration with institutional players. In particular, what emerges from the case is the need to overcome or mitigate prejudices among the key players involved and to find synergies between top-down and bottom-up actions. The hope is that this paper would be a way to learn from others' experiences and contribute to the debate about the effective development of actions surrounding entrepreneurial education.